Safety archetypes identification and behavior simulation for nuclear power plant operation human reliability improvement. (1st September 2022) - Wu, Guanyin; Mao, Yuhe; He, Yifan; Lu, Yi; Jia, Ming; Fu, Shan
Highlights: Identifying an initial set of four system safety archetypes in nuclear power plant operation and proposing a hierarchical model. Better reflecting human error characteristics by considering the interrelationship among performance shaping factors. Providing a mechanical explanation of the operating risk evolution process in nuclear power plant based on a systems-theoretic view. Modeling the path dependence characteristics among performance shaping factors based on the S-shaped "time-risk curve" Promoting stakeholders to concern potential safety impacts of their decisions on nuclear power plant accidents in medium-and-long term vision. Abstract: Safe operation is the foundation and guarantee of the sustainable development of the nuclear power industry. With the continuous improvement of digital nuclear power plant (NPP) design and construction, fewer and fewer accidents are caused solely by mechanical failure. Human factors (HFs) have become the most important cause of NPP accidents. By combing insights from the framework of Human Factor Analysis and Classification System (HFACS) and introducing System Dynamics approach, this paper proposes a human reliability model which identifies four safety archetypes illustrating HF risk mechanisms in NPP operation, captures the PSF interrelationship and breaks through traditional independent PSF analysis. This model focuses on the path dependence characteristics of HF risk accumulation process in a form of S-shaped risk-time curve, and the derived scenario simulations provide suggestions for related stakeholders in nuclear power field to evaluate their decision-making on human reliability improvement better in a medium-and-long term vision.